PENYULUHAN DAN PELATIHAN PEMBUATAN SABUN CAIR EKSTRAK BUNGA ROSELLA (Hibiscus Sabdariffa L) DAN MINYAK ATSIRI LEMON (Citrus Limon Burm F) SEBAGAI ANTIBAKTERI DI SMPN 2 MARGAASIH - Erika Cantika; Cantika, Erika; Muhnandari, Marissa; Siti Julpah, Neng Resti; Rahayu, Helma Pramesti; Khaerunnisa, Yuni; Yulianitas, Ica Dwi; Lilhgaitsha, Agril Balqist; Anisa, Gina; Putri, Aril Diana; Sidik, M Hasbi Subki; Setyoningsih, Wahyu; Aulia, Rini (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2024)
Skin is part of the organ that covers the human body. The skin has many functions such as physical protection, temperature regulation, conductor/receptor of taste sensations, excretion and absorption of substances such as vitamin D. The skin has 3 layers, namely the epidermis, dermis and hypodermis which have special functions and characteristics. Prevention of skin infections can be done by washing the skin using soap that contains antibacterial. The main ingredient used in making soap is Triclocarban, but this ingredient has the side effect of being easily resistant. Therefore, we recommend natural ingredients to avoid resistance, namely using Rosella flowers as an antioxidant and lemons as a germicide and curing irritation. The aim of the activity is to provide training in making antibacterial liquid soap from natural plants as a skin treatment for skin infections that cause disease. The method used is demonstration and presentation of material. Activities were carried out at SMPN 2 Margaasih Kab. Bandung, West Java Province. The activity ran smoothly and received enthusiasm from students, teachers and school staff. From the pre and post test results, it was concluded that there were significant differences after and before the counseling, which means that this counseling and training was useful in increasing insight.